The Scars of Memory: The Biographies of Monument Trees in Central Europe - Browarny, Wojciech (Porównania, 2023)
The author of the article examines monument trees, representing in history and culture traumatic social experiences. Using examples from Central Europe, he describes specific trees and their close environment (surroundings), looking for traces of dramatic events or processes from the past. On this basis, he reconstructs the biomemory of the region, which stores the “scars” of military conflicts, political violence, expulsions or cultural cleansings. The author argues that biomemory can function as an alternative history or counterhistory, preserve local tradition, inspire social practices, and conceptualize the relationship between the ideological, civilizational and organic perception of the natural environment.